Molecular characteristics and expression pattern of the FAR1 gene during spike sprouting in quinoa - Liubin Huang; Lingyuan Zhang; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Xuqin Wang; Yutao Bai; Guofei Jiang; Peng Qin (Scientific Reports)
Abstract FAR-RED IMPAIRED RESPONSE 1 (FAR1) is a class of transposase-derived transcription factors that play a very important role in the initiation of the photosensitive pigment A (phyA) signaling pathway. Despite their importance, the understanding of the function of FAR1 genes in quinoa is still limited, especially regarding how they affect the spike sprouting response. Quinoa has gained global attention in recent years for its health benefits and potential for sustainable agriculture. In our study, the CqFAR1 gene set in quinoa was characterized using HMMER (PF03101) and BLAST analyses, and 87 genes were identified. The 87 CqFAR1 genes were systematically classified into five groups that showed a high degree of conservation in gene structure and motif composition. Tissue expression profiles of the CqFAR1 gene indicated that the CqFAR1 gene plays a key role throughout the growth and development of quinoa, especially at mid (leaf) and end (spike) stages. By RT-qPCR analysis, we observed significant differences in the expression of the CqFAR1 gene at different developmental stages. Notably, the CqFAR1 gene showed significant expression enhancement at the early stage of quinoa spike sprouting. The results are useful for understanding the role of the CqFAR1 gene in quinoa growth and development and provide theoretical support for quinoa breeding.